Did they login? Patterns of anonymous contributions to online communities - Corey Brian Jackson; Kevin Crowston; Carsten Østerlund (Proceedings of the ACM on Human-Computer Interaction, 2018)
Researchers studying user behaviors in online communities often conduct analyses of events collected in system logs, e.g., a system’s record of a comment post or of a contribution. However, analysis of user behaviors is more difficult if users make contributions without being logged-in (i.e., anonymously). Since a user’s account will not be associated with contributions that user makes anonymously, conclusions about user behaviors that look only at attributed actions might not account for a user’s full experience. To understand the impacts of anonymous contributions on research, we conducted an analysis of system logs containing anonymous activities in two online citizen science projects. By linking anonymous events with user IDs we found that (1) many users contribute anonymously, though with varied patterns of contribution; and (2) including anonymous activities alter conclusions made about users’ experience with the project. These results suggest that researchers of human behaviors in online communities should consider the possible impacts of anonymous interaction on their ability to draw conclusions about user behaviors in these settings.